(untitled) (Asian Journal of Pharmaceutics (AJP), 2020)
Aim: The objective of the present investigation was to extract the mucilage from flower petals of Bombax ceiba and explore its use as a promising excipient for Pharmaceutical preparation. The natural polymers have constantly a remarkable property which makes them particular from synthetic polymer and B. ceiba flower mucilage is one such model that shows increasingly important properties making it a helpful excipient for a wide scope of utilizations. Materials and Methods: The flowers of B. ceiba were collected from the Regional Ayurveda Research Institute for Drug Development, Gwalior region of India and were authenticated at the Botanical Survey of India, Central Regional Centre, Allahabad, U.P (Authentication voucher No. B.S.I/C.R.C/TECH./2018-19/559 with Accession No. 103976). B. ceiba flower petals mucilage is isolated by the microwave-assisted method and tablet prepared by experimental runs was designed by Design Expert 10.0.1 (Stat Ease. Inc.) software following full factorial method. 32 full factorial designs were applied for examining two variables (factors) at three levels with a minimum of nine runs. The tablets containing paracetamol as main active constituent were prepared with by a wet granulation method using isolated mucilage in different composition (F1-F9) or starch (F10) or PVP K 30 (F11) as internal binder. Results: The flow properties of the drug excipients mixture were studied in term of bulk density; tapped density; car’s index; and angle of repose to establish the flow property reflect the appropriateness of formulation. All tablet formulations batch evaluated for post-compression parameters have shown acceptable and within the Pharmacopoeial limits of results. The release characteristics of formulations were studied using tablet dissolution test apparatus is paddle type (USP type II) at 50 rpm. The cumulative percent drug release of formulations, i.e., F1, F2, F3, F4, F5, F6, F7, F8, F9, F10, and F11 was 91.31%, 92.67%, 94.22%, 88.83%, 90.36%, 91.11%, 90.54%, 92.11%, 93.98%, 78.66%, and 80.36%, respectively, in 60 min. The result justified that the effect of optimized formulation F3 is significantly more effective than starch and similar effect as synthetic polymer. Conclusions: The results suggest that B. ceiba mucilage could be useful as an alternative binding agent in tablets with better mechanical properties and release profile.